2009
DOI: 10.4103/0972-5229.56050
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function for outcome prediction in severe sepsis and septic shock: An echocardiographic study

Abstract: Left ventricular function and B-type natriuretic peptide (BNP) assessments are used to predict mortality in septic patients. Left atrial function has never been used to prognosticate outcome in septic patients.Objectives:To assess if deterioration of left atrial function in patients with severe sepsis and septic shock could predict mortality.Methods:We studied 30 patients with severe sepsis or septic shock with a mean age of 49.8±16.17. Echocardiographic parameters were measured on admission, Day 4, and Day 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…TTE diagnostic variables have been shown to be predictive of mortality in non-critical care cardiovascular patients with diastolic dysfunction. 11 Landesberg G et al (2015) Studied 105 patients with sepsis and found that, N-terminal pro-B-type natriuretic peptide (NT-pro BNP) strongly correlated with both reduced LVEF and reduced e′-wave velocity, and hs-troponin-T correlated mainly with reduced e'wave with severe sepsis and septic shock. In present study because of resource limitations we have not included cytokines and biomarkers, but there was strong correlation between diastolic dysfunction and mortality in patients with septic shock.…”
Section: Present Studymentioning
confidence: 99%
“…TTE diagnostic variables have been shown to be predictive of mortality in non-critical care cardiovascular patients with diastolic dysfunction. 11 Landesberg G et al (2015) Studied 105 patients with sepsis and found that, N-terminal pro-B-type natriuretic peptide (NT-pro BNP) strongly correlated with both reduced LVEF and reduced e′-wave velocity, and hs-troponin-T correlated mainly with reduced e'wave with severe sepsis and septic shock. In present study because of resource limitations we have not included cytokines and biomarkers, but there was strong correlation between diastolic dysfunction and mortality in patients with septic shock.…”
Section: Present Studymentioning
confidence: 99%
“…However, if this is not true, critical dysfunction may go undetected, and increased mortality in both trauma and septic patients with systolic failure has been observed. 4,5 A depressed EF can also directly impact fluid management and the use of inotrophic agents in the ICU.…”
mentioning
confidence: 99%